Conceptualizing semi-legality in migration research - Kubal, A (International Migration Institute, 2012)
What is semi-legality, and why does it offer a viable alternative to the legality-illegality binary divide? The paper discusses theoretical limits to illegality with reference to migrants – especially those deemed to stand outside the state’s legal system – demonstrating that the division between legal/ illegal is never black or white but woven with different shades of grey: the 'in-between’ statuses of semi-legality. I argue that semi-legality could be viewed as a multi-dimensional space where migrants’ formal relationship with the state interacts with their various forms of agency towards the law. This paper utilizes data stemming from 360 qualitative interviews with international migrants in four European countries. Delineating the conditions of semi-legality I discuss its various empirical contexts: (1) 'incomplete’ responses to regularisation programmes - de facto fulfilling the legalisation conditions, yet facing barriers to formally (de iure) corroborate this; (2) balancing between the temporality of residence in various EU countries: understaying in some and overstaying in others; and (3) the nexus with employment – where migrants’ residence in a country is lawful, but their work exceeds the restrictions permitted by their visas. I juxtapose those against the subjective experiences of semi-legality and migrants’ own interpretations of their position vis-à-vis state legal frameworks.